2016
DOI: 10.1371/journal.pone.0165583
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Gait Deviation on Weight-Bearing Asymmetry and Postural Instability in Children with Unilateral Cerebral Palsy

Abstract: Postural control deficits have been suggested to be a major component of gait disorders in children with cerebral palsy. The purpose of this study was to investigate the relationship between postural stability and treadmill walking, in children with unilateral cerebral palsy, by defining dependence between the posturographic weight-bearing distribution and center of pressure (CoP) sway during quiet standing with Gillette Gait Index and the 16 distinct gait parameters that composed the Gillette Gait Index. Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This finding would be explained by the weight-bearing responses to keep balance and the overrepresentation of those with spastic hemiplegia in our sample (62.8%). A study by Domagalska-Szopa et al 50 on children with unilateral spasticity revealed that their balance difficulties in keeping a standing position were caused by their tendency to load the affected lower limbs excessively or insufficiently. Therefore, it is plausible to think that, when performing TW, individuals with spastic hemiplegia tend to bear their weight on the nonaffected leg, leading to the positive correlations between TW and OLS D variables.…”
Section: Test Reliability and Correlation Analysismentioning
confidence: 99%
“…This finding would be explained by the weight-bearing responses to keep balance and the overrepresentation of those with spastic hemiplegia in our sample (62.8%). A study by Domagalska-Szopa et al 50 on children with unilateral spasticity revealed that their balance difficulties in keeping a standing position were caused by their tendency to load the affected lower limbs excessively or insufficiently. Therefore, it is plausible to think that, when performing TW, individuals with spastic hemiplegia tend to bear their weight on the nonaffected leg, leading to the positive correlations between TW and OLS D variables.…”
Section: Test Reliability and Correlation Analysismentioning
confidence: 99%
“…However, due to the occurrence of further consecutive and compensatory movements (e.g., pelvic obliquity/trunk lean), the internal hip rotation seems to just partially compensate for the lever arm deficit and weak hip abductors [ 34 , 37 ]. Trendelenburg and Duchenne limp generally represent sufficient but energy-consuming compensatory mechanisms to unload weak hip abductors [ 8 , 27 , 32 , 33 , 34 , 38 , 39 ]. Furthermore, other than in bilateral CP (postural/gait disorders in the sagittal plane), patients with unilateral CP predominantly show coronal plane gait disorders [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have clearly indicated that improving COP symmetry in patients with unilateral knee arthritis can improve their walking stability [23]. Experiments have shown that the focus of rehabilitation in patients with unilateral lower extremity is to improve the symmetry of COP displacement and enhance the gait and balance of patients [24].…”
Section: Discussionmentioning
confidence: 99%